Standaryzacja struktury tekstu i jego ukształtowania typograficznego w lubelskich kazaniach pogrzebowych z XVII wieku = Standardization of the text`s Structure and its typographical Shape on the example of Lublin`s Funeral Sermons from 17th century - Sawa, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The printing house, that worked in 1630-1667 in Lublin, published many funeral sermons, five of which are the basis of the present analysis. The structure of the analysed sermons is typical for this type of literary activity. They consist of the title page, the dedication letter and the main text of sermon. On the recto side of title page, there are such pieces of information as: the leitmotiv of the sermon, the name, surname and formal title (honorifc) of the deceased, the name, surname of the preacher with some information about him, the place and time of preach and the address where the sermon was issued.
Keywords: kazania pogrzebowe; struktura tekstu; typografia; funeral sermon; text`s structure; typography